2018
DOI: 10.1186/s13287-017-0763-3
|View full text |Cite
|
Sign up to set email alerts
|

BCN057 induces intestinal stem cell repair and mitigates radiation-induced intestinal injury

Abstract: BackgroundRadiation-induced gastrointestinal syndrome (RIGS) results from the acute loss of intestinal stem cells (ISC), impaired epithelial regeneration, and subsequent loss of the mucosal barrier, resulting in electrolyte imbalance, diarrhea, weight loss, sepsis, and mortality. The high radiosensitivity of the intestinal epithelium limits effective radiotherapy against abdominal malignancies and limits the survival of victims of nuclear accidents or terrorism. Currently, there is no approved therapy to mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 49 publications
2
55
0
Order By: Relevance
“…There are currently no useful in vitro models of intestinal epithelial damage and repair that use primary epithelial cells. An organoid model of irradiation-induced epithelial damage and repair was used previously, [14][15][16][17] however, a careful transcriptional analysis of the repair process has not been performed previously. Here, we describe a model of epithelial regeneration using sublethally irradiated smallintestinal organoids that recapitulates key aspects of epithelial repair after irradiation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently no useful in vitro models of intestinal epithelial damage and repair that use primary epithelial cells. An organoid model of irradiation-induced epithelial damage and repair was used previously, [14][15][16][17] however, a careful transcriptional analysis of the repair process has not been performed previously. Here, we describe a model of epithelial regeneration using sublethally irradiated smallintestinal organoids that recapitulates key aspects of epithelial repair after irradiation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Damage models using organoid culture exposed to irradiation have been developed previously, however, the recovery phase after induction of damage was not characterized extensively. [14][15][16][17] Here, we performed a dose range of g-radiation on intestinal epithelial organoids to identify a sublethal dose that results in a cycle of damage and repair, as measured by the loss and resurgence of expression of intestinal epithelial stem cell markers such as leucine-rich repeat-containing G-protein-coupled receptor 5 (Lgr5) and olfactomedin 4 (Olfm4), as well as morphologic characteristics. Transcriptomic analysis of different time points identified hepatocyte nuclear factor 4a (HNF4a) as one of the upstream regulators of the epithelial response to damage.…”
mentioning
confidence: 99%
“…Developing novel compounds that can mitigate radiation effects is a growing research field. Many different cytokines, growth factors, and inhibitors have been proposed for this function (32)(33)(34)(35)(36)(37)(38). These agents either act on the Wnt pathway necessary for CBC function or otherwise, affect the overall health of intestine after radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are no FDA-approved treatments that can be used to protect against radiation induced damage to the rectal epithelium. Previous research on radiation induced toxicity in small bowel demonstrated that radiation induced loss of intestinal stem cell is the major cause of mucosal damage [4][5][6]. Unlike radiation induced small bowel toxicity majority of the reports on radiation induced rectal injury described radiation induced proctitis /fibrosis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These Bmi1+ve ISCs interconvert with more rapidly proliferating LRG5+ve stem cells known as CBCs that express markers including Lgr5, Olfm4, Lrig1 and Ascl2 [10][11][12][13][14][15]. Both in vivo mice model and ex-vivo organoid model it has been demonstrated that sensitivity of these stem cell are the determining factor for mucosal epithelial response to radiation exposure [4,6]. In small intestine it has been reported that label-retaining stem cells present at the +4 position are more radioresistant than CBCs and functions as a reserve stem cell pool.…”
Section: Introductionmentioning
confidence: 99%